Cartografia dos afetos na covid-19 a partir das timelines discursivas no Facebook - Marcela Tessarolo Bastos (2022)
This doctoral thesis aims to map the affections of Covid-19 from the discursive timelines (MALINI et al, 2020) on Facebook Brazil. For this, we divided the work into four chapters based on a theoretical framework that dialogues with the “affective turn” (CLOUGH, 2007), of studies in the humanities and social sciences, and with digital methods, in the “computational turn in research in Communication” (VIMIEIRO and BARGAS, 2018). Thus, our first chapter deals with human affectivity, based on Espinosa (2016) and his view on fear and hope. To Espinosa (2016), out of fear, people let themselves be dominated by superstition, as happened in the genealogy of several diseases, including Covid-19. We recover fear in the history of humanity (WOLFF, 2007; DELUMAU, 2006; FEBVRE, 2009) and show how contemporaneity is also an era of fear (BAUMAN, 2012). One way humans show affection, including fear, is through narratives propagated on social media platforms. They changed the way each individual communicates and accesses information (JURNO, 2020). So, chapter 2 deals with the platform society and the power of Facebook. Authors highlight the complex gears of platforms, which select and influence the content that will appear on each user’s timeline. We also mapped the main policies adopted by Facebook to contain misinformation about Covid-19 and the controversies among users during the Covid-19 pandemic in Brazil in 2020. The third chapter deals with the changes in journalism with the release of the broadcast hub of content and popularization of the internet and social media platforms, and how this media scenario increases the spread of disinformation. It also discusses narratives, events and discursive timelines (MALINI et al, 2020). Finally, it deals with necropolitics and necropower (MBEMBE, 2016, p. 146), addresses digital populism (CESARINO, 2019;2020), and disinformation as a political communication strategy. The fourth chapter brings our empirical analysis of public posts from four discursive milestones of 2020, collected in the CrowdTangle tool, from Facebook Brazil, the most used platform for searching for information in the country (DIGITAL NEWS REPORT 2020, 2021). We read and analyze the posts of the discursive timeline, which displaces the meanings in each period (MALINI et al, 2020), and we categorized the actors in the posts, not always complying with self-definitions. Through graphs, we visually present the networks formed based on principles of social network analysis (RECUERO, 2017). We also collected testimony from five survivors, in a descent into everyday life (DAS, 2020) to map affections not expressed on Facebook. Feelings of loneliness, helplessness and anxiety were common among survivors. Since its genealogy, controversial narratives have circulated and made it difficult to fight the disease. On Facebook, fear and hope mobilized controversies during the Covid-19 pandemic, such as criticism or defense of social isolation, and misinformation about vaccines that emerged as promising. There was no consensus on the fight against Covid-19 in Brazil. Politicians, doctors and ordinary people have fueled disinformation narratives. The far right promoted hope in fake medicines and fear of vaccines. In this scenario, communities, Facebook groups and blogs, which imitate the model of traditional journalism, played an important role in the propagation of false hopes for a cure in medicines whose scientific studies have already shown their ineffectiveness in combating Covid-19.